The influence of imperfect interfaces on the measurable effective properties of ceramic composites. Issue 9 (2nd September 2022) - Bolzon, Gabriella; Pitchai, Pandi
ABSTRACT: This work evaluates the influence of the interface characteristics on the measurable quantities that reflect the overall response of ceramic composites. The situations that may lead to the misinterpretation of the experimental results are evidenced. The study is carried out on representative volume elements (RVEs) of periodic microstructures with either perfect adhesion or pure frictional coupling between the matrix and the reinforcement. These alternatives may constitute the initial and the final material configuration in the presence of damaging processes. The mechanical response to common characterization tests is reproduced by numerical analyses, and measurable quantities are evaluated by computational homogenization procedures. Different material combinations with fiber or particle inclusions are analyzed. The case of porous composites is also introduced for comparison purposes. Overall stresses and strains are not proportional in the presence of frictional interfaces. It is however shown that the deviation from linearity is slight and prone to be confused with experimental inaccuracies, e.g. due to the initial adjustment of the testing devices. The effect on the effective material proprieties is significant, though. Graphical abstract: uf0001